Evaluación de riesgo químico y su incidencia en los trabajadores del área de no Catalíticas 1 y 2 en la refinería estatal de esmeraldas, propuesta de un modelo de gestión de seguridad para minimizar los efectos de la exposición. - Bassantes Segovia, Juan Israel (2017)
The purpose of this study is to assess the chemical risk and its impact on workers in area No. Catalicas 1 and 2 in the state refinery of Esmeraldas, with the results obtained, a safety management model is proposed, which will allow minimizing the effects of the exposure to which workers are exposed ...